2015
DOI: 10.1111/hir.12100
|View full text |Cite
|
Sign up to set email alerts
|

Fear of cancer is associated with cancer information seeking, scanning and avoiding: a cross‐sectional study among cancer diagnosed and non‐diagnosed individuals

Abstract: Fear of cancer is positively associated with cancer information acquisition and avoiding behaviour. This suggests that fear of cancer predicts different behaviours in different individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
4
27
0
Order By: Relevance
“…Although previous studies suggest that people may be “in two minds” about cancer, our study shows that the first response to cancer is often negative. Cancer fear and fatalism undermine cancer prevention and early detection behaviours, and further research is needed to explore how these attitudes are formed and how they may be changed to increase the effectiveness of cancer control strategies, especially in groups with lower levels of education. Examples of effective interventions to address fatalistic attitudes in the US included video interventions aimed at targeting barriers to cancer screening or presenting narratives of cancer survivors .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies suggest that people may be “in two minds” about cancer, our study shows that the first response to cancer is often negative. Cancer fear and fatalism undermine cancer prevention and early detection behaviours, and further research is needed to explore how these attitudes are formed and how they may be changed to increase the effectiveness of cancer control strategies, especially in groups with lower levels of education. Examples of effective interventions to address fatalistic attitudes in the US included video interventions aimed at targeting barriers to cancer screening or presenting narratives of cancer survivors .…”
Section: Discussionmentioning
confidence: 99%
“…Negative beliefs about cancer adversely affect cancer‐related behaviours. Cancer fatalism (the belief that cancer is inevitably fatal), has consistently been shown to deter individuals from attending cancer screening, help‐seeking for possible cancer symptoms, and attending to cancer‐related information . Such fatalistic beliefs are more prevalent in certain subgroups of the population, including those from more deprived backgrounds .…”
Section: Introductionmentioning
confidence: 99%
“…Interview participants were disinterested in looking up symptoms online, explaining that they did not want to worry themselves, adding that online symptom checkers tend to put the worst possible scenario front and center. A 2015 study exploring the relationship between cancer worry and information seeking found that worry is associated with cancer information acquisition for some, and avoidance behavior for others (Nelissen et al, 2015). That study surveyed a group of individuals with a cancer diagnoses and a group of individuals without cancer and found that a cancer diagnosis did not moderate an individual's information seeking behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Wikipedia is now an excellent and quickly accessible source of information for statistical analysis and can be a useful resource for quickly checking details. 1 However, for more detailed support, you will probably need a more in-depth statistics book. Liwen Vaughan's book 'Statistical Methods for the Information Professional' remains a key resource for the library and information sector 2 and, using examples from the information science sector, can help you identify what type of data you have (nominal, ordinal, interval or ratio data) and which statistical tests are most appropriate to use (chi-square, t-test, ANOVA, etc.…”
Section: Tell a Storymentioning
confidence: 99%
“…Nelisson et al 1 used a questionnaire survey in investigating information behaviour. They recruited a convenience sample of 621 cancer diagnosed and 1387 non-diagnosed individuals.…”
Section: Referencesmentioning
confidence: 99%